Modelling Water and Pesticide Transport in Soil with MACRO 5.2: Calibration with Lysimetric Data - Kolupaeva, Victoria; Kokoreva, Anna; Belik, Alexandra; Bolotov, Andrei; Glinushkin, Alexey (Agriculture (Basel), 2022)
Assessing the risk of using pesticides for the environment in general, and for groundwater in particular, necessitates prediction of pesticide migration. For this purpose, mathematical models of pesticide behavior are utilized, which must be parameterized and calibrated based on experimental data to make them perform properly. The behavior of the pesticide cyantraniliprole was examined in a long-term lysimetric experiment. The MACRO 5.2 dual porosity model was calibrated based on the percolate and the levels of pesticides in the soil profile and percolate. Despite employing experimentally verified soil parameters and pedotransfer functions (PTF), the model must be calibrated for percolation. This is due to the model’s properties as well as the complexity of the soil as an object of study, and its pore space, which is subject to daily and annual fluctuations. It is the parameters that describe the structure of the pore space that need to be calibrated. Calibrating for pesticide concentrations required a minor revision of the sorption and transformation rates, as well as an increase in the dispersivity and ASCALE values.